THE EMERGENCE AND DEVELOPMENT OF THE RESPONSIBILITY OF MILITARY PERSONNEL FOR VIOLATING ANTI-CORRUPTION LAWS BEFORE THE XX CENTURY - S. Tereshchuk (Вестник университета, 2019)
The emergence and development of the responsibility of military men for violations of legislation on countering corruption (in the period of the XIV century up to XX century.) have been analyzed. The main regulatory legal acts, adopted by the rulers of Russia and aimed at combating corruption among officials, as well as officials of the military administration have been considered. In addition, the main conditions for the emergence and preservation of corruption in the Russian Empire have been examined. A critical assessment to the implementation of local government by appointing vicars without establishing a money allowance for them (the «feeding» system has been given.